THE RELATION BETWEEN DEPRESSION AND PERCEIVED SOCIAL SUPPORT IN NURSING STUDENTS IN THE CONTEXT OF SUICIDAL BEHAVIORS - Daniel Martínez-Esquivel; Patsy Quesada-Carballo; Yerlin Quesada-Rodríguez; Derby Muñoz-Rojas; Ana Laura Solano-López (Universidade Federal do Paraná, 2022)
Objective: to determine the relationship between depression and perceived social support in nursing students in the context of suicidal behaviors. Method: secondary analysis of data from a previous study. Sample from the census of nursing students in Costa Rica. Data collection performed by LimeSurveyduring 2020 by means of self-administered questionnaire composed of sociodemographic data section, Beck-II depression inventory and multidimensional scale of perceived social support. Descriptive analysis and Pearson correlation were used. Results: The majority were female (79.5%), with a mean age of 22.15 years; 85.8% reported mild to minimal depression; 92.2% reported high perceived social support. A significant inverse correlation was identified between level of depression and perceived social support (r=-0.44, p<0.01). Conclusion: The understanding about mental health conditions by nursing science is broadened to improve care practices in a specific group.